Penerapan Model Pembelajaran Think Pair Share Dalam Meningkatkan Aktivitas Belajar Siswa Sosiologi Kelas XI IPS 1 Di SMAN 1 Kecamatan Akabiluru Kabupaten Lima Puluh Kota - Rifi Yolanda; Nurlizawati Nurlizawati (Universitas Negeri Padang, 2022)
This research is motivated by the low level of student learning activities that affect student learning outcomes in sociology in class XI IPS SMAN 1 Akabiluru District, the low learning activity is influenced by several factors, one of which is learning strategies. This needs to be corrected by the teacher, one way to improve it is by applying the think pair share learning model in the student learning process, this study aims to analyze the effect of the think pair share learning model in improving student learning activities in class XI IPS 1 SMAN 1 Akabiluru District. the type of research that will be used is Classroom Action Research (CAR) with the model from Kemmis and Mc. Taggart. Data collection techniques used are observation, interviews and tests. The research instruments that the researcher used were observation sheets and tests. The data analysis technique used is descriptive quantitative with a sample of 32 students in class XI IPS 1. The theory used in this study is Behavioristic according to Thorndike. The results of this study indicate that there is an increase in learning activities using the think pair share learning model. This is indicated by the average percentage of the first cycle of 36.1%, in the second cycle there was an increase of 71.8% so it can be concluded that using the learning model can increase student learning activities and also have an influence on learning outcomes with the percentage of the pretest level of completeness 31.3% and at posttest 75%. This happens because students are required to complete individual and group assignments that develop students' thinking skills so that students are able to think critically and make students active in learning activities.